Variable Domain N-Linked Glycans Acquired During Antigen-Specific Immune Responses Can Contribute to Immunoglobulin G Antibody Stability - van de Bovenkamp, Fleur S.; Derksen, Ninotska I. L.; van Breemen, Mariëlle J.; de Taeye, Steven W.; Ooijevaar-de Heer, Pleuni; Sanders, Rogier W.; Rispens, Theo (Frontiers in Immunology, 2018)
Immunoglobulin G (IgG) can contain N-linked glycans in the variable domains, the so-called Fab glycans, in addition to the Fc glycans in the CH2 domains. These Fab glycans are acquired following introduction of N-glycosylation sites during somatic hypermutation and contribute to antibody diversification. We investigated whether Fab glycans may – in addition to affecting antigen binding – contribute to antibody stability. By analyzing thermal unfolding profiles of antibodies with or without Fab glycans, we demonstrate that introduction of Fab glycans can improve antibody stability. Strikingly, removal of Fab glycans naturally acquired during antigen-specific immune responses can deteriorate antibody stability, suggesting in vivo selection of stable, glycosylated antibodies. Collectively, our data show that variable domain N-linked glycans acquired during somatic hypermutation can contribute to IgG antibody stability. These findings indicate that introducing Fab glycans may represent a mechanism to improve therapeutic/diagnostic antibody stability.